2017
DOI: 10.1007/s11259-017-9698-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community and ovine host response varies with early and late stages of Haemonchus contortus infection

Abstract: The interactions between gastric microbiota, ovine host, and Haemonchus contortus portray the ovine gastric environment as a complex ecosystem, where all factors play a pertinent role in fine-tuning each other and in haemeostasis. We delineated the impact of early and late Haemonchus infection on abomasal and ruminal microbial community, as well as the ovine host. Twelve, parasite-naive lambs were divided into four groups, 7 days post-infection (dpi) and time-matched uninfected-control groups; 50 dpi and time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 58 publications
6
42
2
6
Order By: Relevance
“…Indeed, whilst our study used faecal microbial composition as a proxy of bacterial populations inhabiting other compartments of the sheep GI tract (cf. 44; reviewed by 45), selected alterations observed herein are consistent with previous descriptions of qualitative and quantitative changes of bacterial populations inhabiting the abomasa of ruminants infected with GI nematodes [41][42][43], and thus provide support to the validity of our findings. Taken together, these data confirm the major role of helminth colonisation in gut microbiome re-modelling, and that experimental vaccination prior to parasite challenge resulted in further alterations of the gut microbial profiles of Vac/Tc+ sheep at the end of the study period, which were likely to result from the effect of vaccination on worm survival.…”
Section: Experimental Infection Outcomessupporting
confidence: 91%
“…Indeed, whilst our study used faecal microbial composition as a proxy of bacterial populations inhabiting other compartments of the sheep GI tract (cf. 44; reviewed by 45), selected alterations observed herein are consistent with previous descriptions of qualitative and quantitative changes of bacterial populations inhabiting the abomasa of ruminants infected with GI nematodes [41][42][43], and thus provide support to the validity of our findings. Taken together, these data confirm the major role of helminth colonisation in gut microbiome re-modelling, and that experimental vaccination prior to parasite challenge resulted in further alterations of the gut microbial profiles of Vac/Tc+ sheep at the end of the study period, which were likely to result from the effect of vaccination on worm survival.…”
Section: Experimental Infection Outcomessupporting
confidence: 91%
“…Notably, previous work, albeit within goats, showed that H. contortus infection did not result in a shift in abomasal microbiome diversity; however, an effect was seen on the abundances of several bacterial species (41). Contrastingly, infection of lambs with H. contortus alone was found to increase microbiome diversity in the abomasum (42). Differences observed may be attributable to inter-species differences and/or inter-study differences.…”
Section: Oral Ingestion Of Engineered E Coli By Larvae In Vitromentioning
confidence: 75%
“…It may be due to higher susceptibility of Entodinia to H. contortus infection. H. contortus infection alters microbial community composition and diversity, which facilitates the parasite survival and reproduction [50]. Variations in ruminal microbiota composition…”
Section: Discussionmentioning
confidence: 99%